الذكاءات المتعددة وعلاقتها بمهارات التعلّم الرقمي في ضوء التحول التربوي المعاصر (Comprehensive Journal of Science, 2025)
This study aims to explore the relationship between multiple intelligences and digital learning skills in light of contemporary educational transformation, and to reveal their role in enhancing learners’ capacities to meet the demands of the digital era. The study employed the descriptive-analytical method through a review of theoretical concepts and an analysis of relevant educational trends. The findings indicate that the development of each type of intelligence contributes to the advancement of specific digital skills; for instance, visual–spatial intelligence fosters interaction with virtual reality, linguistic intelligence supports communication through digital platforms, and logical–mathematical intelligence enhances learners’ efficiency in programming and problem-solving. Moreover, the integration of multiple intelligences enriches digital learning by promoting creativity, critical thinking, and collaborative learning. The results also highlight that educational transformation extends beyond the digitization of tools, requiring instead a new pedagogical philosophy that accommodates learners’ cognitive diversity. The study concludes with several recommendations, most notably: the integration of multiple intelligences into digital curriculum design in alignment with individual differences, the utilization of advanced technologies such as virtual reality and simulations to support different intelligences, training teachers on flexible digital teaching strategies, and conducting applied studies to identify practical mechanisms for embedding multiple intelligences within digital learning environments.
Keywords: Multiple Intelligences – Digital Learning – Educational Transformation